Performance Evaluation of Softened Two-Bit Hard Combination Scheme for Cooperative Spectrum Sensing - Abdulhamid, Mohanad (Fakultas Teknik Universitas Negeri Surabaya, 2024)
Cooperative spectrum sensing is one of the main approaches to improve the efficiency of spectrum utilization in cognitive radio networks. This study aims to evaluate the performance of a softened hard two-bit combining scheme in cooperative spectrum sensing. This scheme combines the sensing information from multiple secondary users by utilizing a softened two-bit representation to improve the detection accuracy and reduce the error probability. The evaluation is carried out through simulations under various channel conditions, such as AWGN and Rayleigh fading channels, considering factors such as signal-to-noise ratio (SNR) and the number of secondary users. The results show that this scheme is able to significantly improve the detection probability (Pd) compared to the conventional hard combination method, especially under low SNR conditions. In addition, this scheme shows efficiency in reducing communication overhead, making it a promising solution for the implementation of reliable spectrum sensing in cognitive radio networks. This paper measures the performance of cooperative spectrum sensing, over Rayleigh fading channel and additive white Gaussian noise, based on softened two-bit hard combination scheme. Two measures based on energy detection are considered including effect of false alarm probability, and effect of number of users. Simulation results show that the detection probability increases with the increase of false alarm probability, number of users, and signal-to-noise-ratio. Keyword: Softened two-bit hard combination scheme, Cooperative spectrum sensing, Cognitive radio